Aspectos fonéticos, morfossintáticos e lexicais do falar de Caiana dos Crioulos. - Lima, Fernanda Barboza de (2010)
The present research deals with the African contribution in the process of the Portuguese formation spoken in Brazil, which has as the study object the negro community called Caiana dos Crioulos , located in the city of Alagoa Grande , in the Mesorregião of the Paraiban Agreste. In this study we analyzed the phonetics, morphosyntatics and lexical particularities in the Caiana s community, identifying in this locality linguistics phenomena understood as contact evidences with African languages. We want through this research to contribute with the discussions about the Popular Portuguese formation in Brazil and also, with the comprehension of the spoken language in brazilian s rural district. We used as methodological procedures, the fold research, where we collected individuals interview guided according to the sociolinguistics models, searching in the common points among the Sociolinguistics, Ethno linguistics and Dialectology, the theoretical support which is necessary to our study. The developed reflections in this research want to contribute with the scientific literary production on the negro s history in Brazil, in a moment in which the necessity of the historical statement identity of this kind of people rise.